Impact of the COVID-19 Pandemic on Gastroenterology Training in India - Sonika, Ujjwal; Sachdeva, Sanjeev; Kumar, Ajay; Srivastava, Siddharth; Dahale, Amol; Sharma, Barjesh Chander; Kumar, Manish; Pandey, Toshali; Yadav, Devesh Prakash; Maharshi, Sudhir; Nair, Sandeep V.; Dalal, Ashok (Journal of Digestive Endoscopy, 2022)
Introduction The coronavirus disease 2019 (COVID-19) pandemic has affected the healthcare system. The residents who are at the frontline of this pandemic have suffered the most. The extent of the training loss due to the COVID-19 pandemic on gastroenterology (GE) training is not studied in India.Methods We designed a 36-question based google survey and distributed it to the GE residents all across India, via email. All the responses collected were analyzed using appropriate statistical methods.Results A total of 140 responses were received. No significant decrease in teaching sessions/ classes was reported. Most of the residents (83.5%) reported inability to complete the target thesis enrolment. The number of patients seen by the residents in outpatient department, patients managed in wards and endoscopic procedures done by residents have decreased significantly (p-valve <0.001 for all). An overwhelming 89.9% (n = 125) of the GE residents were posted for COVID-19 duties. Almost half (50.4%) of them were COVID-19 positive.Conclusion The COVID-19 pandemic has affected the training of GE residents in India immensely and an extension period of 3 months may be offered to them.
Keywords: COVID-19; gastroenterology; medical training; endoscopy